A LAB of Her Own: A Phenomenological Study of a Student Lab Assistant Research Program and Its Impact on Female High School Participants - Cantrell, Brittney Denier (My University, 2018)
The Every Student Succeeds Act of 2015 implores educators to increase female access to and involvement in Science, Technology, Engineering, and Mathematics (STEM) programs in order to improve the diversity of the STEM workforce. Within the literature, it is suggested females who have access to pre-collegiate STEM opportunities are more likely to matriculate in collegiate STEM degree programs. This phenomenological study evaluated the experiences of five female college students who participated in a Student Lab Assistant Research Program (LAB) during high school. To elicit information about the impact of the LAB on female students’ beliefs and interests in STEM, each student engaged in interviews following Seidman’s three-interview series framework. Data was coded and analyzed using Moustakas’ modification of the Stevick-Colaizzi-Keen Method of Analysis of Phenomenological Data. Analysis of data resulted in two core themes emerging as impactful components of the LAB including active learning with real world applications and opportunities for skills acquisition and influential relationships altering perceptions and science attitudes. Findings align with environmental, behavioral, and personal variables known to positively affect choice behaviors as described by Lent, Brown, and Hackett’s Social Cognitive Career Theory. Participation in the LAB positively contributed to female students’ choice to major in STEM degree programs in college. This study offers suggestions for implementation of the LAB in a traditional high school setting. Further research is needed on the lasting impact of the LAB and other pre-collegiate STEM opportunities as viable nontraditional science programs with potential to plumb the leaky STEM pipeline. Keywords: choice, female, high school, matriculation, phenomenological, pre-collegiate, programs, qualitative, science, secondary, Social Cognitive Career Theory, STEM, STEM pipeline
Chapter I: INTRODUCTION 1 | Overview 1 | Background 2 | STEM Forecasts 4 | Statement of the Problem 8 | Purpose of the Study 9 | Significance of the Study 10 | Key Terminology 12 | Chapter II: REVIEW OF LITERATURE 14 | Introduction 14 | The Need for More STEM Graduates 14 | Meaningful Exposure 15 | STEM Program Characteristics 15 | Existing STEM Programs 18 | Learning Communities 19 | STEM Camps, Clubs, and After-School Programs 21 | In-School STEM Programs 22 | Characteristics of Effective STEM Programs 24 | Science Attitudes 25 | Self-Perception, Self-Confidence and Self-Doubt 25 | Stereotypes and Gender Bias 28 | Role Models and Mentoring 30 | Project-Based Work, Individualized Education, and Choice Behaviors 32 | Soft Skills Integration 34 | Active Learning and Real World Application 36 | Theoretical Framework 37 | Chapter III: METHODOLOGY 43 | Statement of Purpose 43 | Research and Design Rationale 44 | Research Questions 46 | Role of Researcher 47 | Methodology 50 | Site and Participant Selection 52 | Background of the LAB 55 | Overview 55 | Application to the LAB 56 | Selection 57 | Placement 57 | Research Site and LAB Program History 58 | Program Goals 62 | Recommendations for Implementation of the LAB 63 | Data Collection Procedures 64 | Data Analysis Plan 67 | Credibility 75 | Trustworthiness 75 | Limitations 78 | Delimitations 79 | Protection of Human Participants 80 | Chapter IV: FINDINGS 82 | Introduction 82 | Overview of Participants 83 | Participant 1 Narrative: Ada-Lived Experience 85 | Biographical Information 85 | History with STEM 85 | LAB Experience 87 | Impact of LAB 90 | Connections Between LAB and Life 91 | Suggested LAB Improvements 92 | Participant 2 Narrative: Mason-Lived Experience 93 | Biographical Information 93 | History with STEM 93 | LAB Experience 95 | Impact of LAB 98 | Connections Between LAB and Life 99 | Suggested LAB Improvements 100 | Participant 3 Narrative: Nina-Lived Experience 101 | Biographical Information 101 | History with STEM 101 | LAB Experience 104 | Impact of LAB 107 | Connections Between LAB and Life 109 | Suggested LAB Improvements 109 | Participant 4 Narrative: Stella-Lived Experience 110 | Biographical Information 110 | History with STEM 111 | LAB Experience 112 | Impact of LAB 114 | Connections Between LAB and Life 116 | Suggested LAB Improvements 117 | Participant 5 Narrative: Stephanie-Lived Experience 118 | Biographical Information 118 | History with STEM 118 | LAB Experience 120 | Impact of LAB 122 | Connections Between LAB and Life 123 | Suggested LAB Improvements 124 | Data Analysis 125 | Data Coding 126 | Emerging Themes 128 | Overview of Theme One 129 | Overview of Theme Two 130 | Theme 1: Active Learning with Real World Applications and Opportunities for Skills Acquisition 131 | Active Learning 131 | Access 132 | Real World Application 133 | Skills Acquisition 134 | Theme 2: Influential Relationships Altering Perception and Science Attitudes 137 | Mentor and Role Model Influences 137 | Relationships and Community 141 | Attitudes 142 | Perceptions 145 | Summary of Findings 148 | Conclusions 150 | Chapter V: CONCLUSIONS 152 | Introduction 152 | Summary of Findings 153 | Connections to the Literature 156 | Significance of the Findings 163 | Implications of the Findings for Practice 165 | Recommendations for Future Research 170 | Additional Considerations 172 | Conclusions 173 | REFERENCES 175 | APPENDIX A: Interview Protocol Adapted from Seidman 200 | APPENDIX B: Recruitment Flyer 203 | APPENDIX C: Qualifying Questionnaire 205 | APPENDIX D: Email to Potential Participants 207 | APPENDIX E: Research Consent Document 209 | APPENDIX F: Confidentiality Agreement for Transcriptionist 211 | APPENDIX G: Analysis of Phenomenological Data 213 | APPENDIX H: Protecting Human Research Participants 215 | APPENDIX I: IRB Approval 217 |
Keywords: High school girls; Science, Technology, Engineering, and Mathematics Education; Education; Science--Study and Teaching.(Secondary)